مدى شرعية إجهاض الجنين المشوه : رؤية إسلامية - معلم، عبد الرحمن أحمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
With the advancement of the medical science, it has been discovered that fetus can be affected due to deformities and other defects. This study aims at investigating the Shari'ah aspect of aborting a deformed child. The study highlights the concept of abortion, fetus and deformity within the context of the terminologies used by Fuqaha (Muslim Jurists) and physicians. The study shows that the Shari'ah texts have explained the stages of the development of the embryo, beginning from the sperm to the infusion of spirit into the fetus. It also shows how this development is explained in the science of embryology. The researcher discusses the origin of human life (from the time the spirit is infused), focusing on the ahadith that have been reported and the various opinions of scholars regarding the issue. The study also includes explanation about the types, causes and harmful effects of abortion. The researcher has explained that numerous factors; both internal and external, can lead to child deformity. Furthermore, he discusses the rulings related to the abortion of a deformed child, be it prior to the infusion of the spirit or thereafter, citing arguments and evidences from contemporary scholars. The study has relied on the inductive method, through which the texts and the views of the scholars related to the subject were compiled. Subsequently, the comparative analytical method was used to analyze the Shari'ah texts and to compare the views of contemporary scholars and their evidences in order to derive a general Shari'ah ruling on the subject. The study has concluded that it is unlawful to abort a fetus that is lightly deformed and can be treated; whether such an abortion is prior to the infusion of the spirit or after the infusion. The researcher preponderates that it is permissible to abort a deformed child subject to certain conditions, such as that the deformity is severe and incurable, the diagnosis is done at a stage prior to the infusion of the spirit, the doctors are just and are at least two in number and permission for the abortion is obtained from the spouses and, so on.